2018
DOI: 10.1371/journal.pone.0190602
|View full text |Cite
|
Sign up to set email alerts
|

From early stress to 12-month development in very preterm infants: Preliminary findings on epigenetic mechanisms and brain growth

Abstract: Very preterm (VPT) infants admitted to Neonatal Intensive Care Unit (NICU) are at risk for altered brain growth and less-than-optimal socio-emotional development. Recent research suggests that early NICU-related stress contributes to socio-emotional impairments in VPT infants at 3 months through epigenetic regulation (i.e., DNA methylation) of the serotonin transporter gene (SLC6A4). In the present longitudinal study we assessed: (a) the effects of NICU-related stress and SLC6A4 methylation variations from bir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
79
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(82 citation statements)
references
References 55 publications
2
79
0
1
Order By: Relevance
“…Most reported study participants were adults (n = 7769) while far fewer were children (n = 727 aged between 2 and 18 and 633 under the age of 2). Of the 37 studies, only nine included data gathered in childhood, and seven of these included a longitudinal follow-up [7,9,[16][17][18][19][20]. Table 1 shows further details of these studies.…”
Section: Resultsmentioning
confidence: 99%
“…Most reported study participants were adults (n = 7769) while far fewer were children (n = 727 aged between 2 and 18 and 633 under the age of 2). Of the 37 studies, only nine included data gathered in childhood, and seven of these included a longitudinal follow-up [7,9,[16][17][18][19][20]. Table 1 shows further details of these studies.…”
Section: Resultsmentioning
confidence: 99%
“…Two glucocorticoids that play significant roles in neonatal outcomes are corticosterone and cortisol, both of which have properties that are beneficial when released in response to short-term stress but become detrimental when the body is exposed to elevated levels over a prolonged period of time. Elevated levels of corticosterone over a prolonged period of time have been found to result in increased levels of glutamate, which contributes to overstimulation of neurons, neuronal cell death (Mooney-Leber & Brummelte, 2017), and ultimately poor brain growth and structural changes to the brain (Fumagalli et al, 2018). These changes in response to prolonged stress likely contribute to some of the long-term neurodevelopmental abnormalities in infants who survive being critically ill (Cong et al, 2017;Fumagalli et al, 2018;Smith et al, 2011).…”
Section: Physiologic Response To High Levels Of Stressmentioning
confidence: 99%
“…In addition, we demonstrate how the proposed early intervention strategy positively modulates short-term infants' neurodevelopment. In this regard, it is already reported that maternal separation and excessive sensory exposure, induced by NICU environment, represent adverse early life events experienced by preterm infants, that can affect the epigenetic regulation and impact on gene expression in the brain (56)(57)(58).…”
Section: Discussionmentioning
confidence: 99%